2016
DOI: 10.1371/journal.pone.0154329
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota and Microbial Metabolites Are Changed in a Pig Model Fed a High-Fat/Low-Fiber or a Low-Fat/High-Fiber Diet

Abstract: The intestinal microbiota and its metabolites appear to be an important factor for gastrointestinal function and health. However, research is still needed to further elaborate potential relationships between nutrition, gut microbiota and host’s health by means of a suitable animal model. The present study examined the effect of two different diets on microbial composition and activity by using the pig as a model for humans. Eight pigs were equally allotted to two treatments, either fed a low-fat/high-fiber (LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 67 publications
9
105
3
2
Order By: Relevance
“…Bacteroidetes and Firmicutes were the most abundant in the colonic digesta which is in agreement with a metagenomic analysis in microbial diversity of swine gut (Burrough, Arruda, Patience, & Plummer, 2015;Heinritz et al, 2016;Jin, Ye, Jin-zhao, Zhi-jiang, & Huan, 2017). Bacteroidetes and Firmicutes were the most abundant in the colonic digesta which is in agreement with a metagenomic analysis in microbial diversity of swine gut (Burrough, Arruda, Patience, & Plummer, 2015;Heinritz et al, 2016;Jin, Ye, Jin-zhao, Zhi-jiang, & Huan, 2017).…”
Section: Rice Distillers' By-product and Colonic Microbiota Identifsupporting
confidence: 86%
See 2 more Smart Citations
“…Bacteroidetes and Firmicutes were the most abundant in the colonic digesta which is in agreement with a metagenomic analysis in microbial diversity of swine gut (Burrough, Arruda, Patience, & Plummer, 2015;Heinritz et al, 2016;Jin, Ye, Jin-zhao, Zhi-jiang, & Huan, 2017). Bacteroidetes and Firmicutes were the most abundant in the colonic digesta which is in agreement with a metagenomic analysis in microbial diversity of swine gut (Burrough, Arruda, Patience, & Plummer, 2015;Heinritz et al, 2016;Jin, Ye, Jin-zhao, Zhi-jiang, & Huan, 2017).…”
Section: Rice Distillers' By-product and Colonic Microbiota Identifsupporting
confidence: 86%
“…Moreover, a high proportion (95%) of produced OA was probably rapidly absorbed by the colonocytes and while the remaining (about 5%) was secreted through the feces (den Besten et al, 2013;Heinritz et al, 2016). Moreover, a high proportion (95%) of produced OA was probably rapidly absorbed by the colonocytes and while the remaining (about 5%) was secreted through the feces (den Besten et al, 2013;Heinritz et al, 2016).…”
Section: Rice Distillers' By-product and Colonic Microbiota Identifmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, changes to the normally-occurring gut bacteria are associated with reduced metabolite and/or peptide production, impaired nutrient absorption, diminished SCFA production, and a proinflammatory state (Cani et al 2008; Ding, et al 2010; Heinritz, et al 2016; Ridaura, et al 2013; Samuel, et al 2008). Several studies have even indicated that HFD-induced dysbiosis promotes intestinal inflammation that precedes obesity and other metabolic diseases (Bleau C1 2015 ; Ding et al 2010).…”
Section: Nutrients and The Regulation Of Metabolic Homeostasismentioning
confidence: 99%
“…For instance, high fiber diets have been associated with the increases in both fecal 61,62 and circulating 63 levels of SCFAs. Another study of humans on a high protein diets saw an increase in levels of the carcinogenic N -nitroso compounds compared to a maintenance diet, thought to be driven by increased protein fermentation and decreased carbohydrate fermentation by colonic microbiota 62 .…”
Section: Linking Microbiome/metabolome With the Exposomementioning
confidence: 99%